The complete sequence of the chloroplast genome of the green microalga Lobosphaera (Parietochloris) incisa. (3rd May 2016) - Tourasse, Nicolas J.; Barbi, Tommaso; Waterhouse, Janet C.; Shtaida, Nastassia; Leu, Stefan; Boussiba, Sammy; Purton, Saul; Vallon, Olivier
Abstract: We hereby report the complete chloroplast genome sequence of the green unicellular alga Lobosphaera ( Parietochloris ) incisa (strain SAG 2468). The genome consists of a circular chromosome of 156, 028 bp, which is 72% A-T rich and does not contain a large rRNA-encoding inverted repeat. It is predicted to encode a total of 111 genes including 78 protein-coding, three rRNA, and 30 tRNA genes. The genome sequence also carries a self-splicing group I intron and a group II intron remnant. Overall, the gene and intron content of the L. incisa chloroplast genome is highly similar to that of other species of Trebouxiophyceae. In contrast, the L. incisa chloroplast genome harbors 88 copies of various intergenic dispersed DNA repeat sequences that are all unique to L. incisa .